Palmitoylation in cancer: decoding its roles in signal transduction, tumor immunity, and emerging therapeutic opportunities - Lu, Qiguang; Wu, Jiasheng; Yu, Xiaoyan; Qian, Juanjuan; Song, Zhengwei (Frontiers in Immunology, 2025)
Palmitoylation, a reversible post-translational modification involving the attachment of palmitic acid to cysteine residues of proteins, plays a critical role in the regulation of protein localization, stability, and function. Recent studies have revealed its significant involvement in various oncogenic processes, including tumor initiation, progression, metastasis, and immune evasion. This review comprehensively explores the molecular mechanisms of palmitoylation and its functional implications in different types of tumors. We discuss how palmitoylation modulates key signaling pathways such as Ras and Wnt/β-catenin, influencing tumor cell behavior and the tumor microenvironment. Additionally, we examine the impact of palmitoylation on anti-tumor immunity and its potential as a therapeutic target. Understanding the intricate roles of palmitoylation in cancer biology not only advances our knowledge of tumor pathogenesis but also opens new avenues for targeted cancer therapies. Future research directions and clinical applications are also highlighted to guide the development of novel interventions.